Oxidized Albumin and Cartilage Acidic Protein-1 as Blood Biomarkers to Predict Ischemic Stroke Outcomes - Takahiro Kuwashiro (Frontiers Media S.A., 2021)
Background: There is high demand for blood biomarkers that reflect the therapeutic response or predict the outcomes of patients with acute ischemic stroke (AIS); however, few biomarkers have been evidentially verified to date. This study evaluated two proteins, oxidized albumin (OxHSA) and cartilage acidic protein-1 (CRTAC1), as potential prognostic markers of AIS.Methods: The ratio of OxHSA to normal albumin (%OxHSA) and the level of CRTAC1 in the sera of 74 AIS patients were analyzed on admission (day 0), and at 1 and 7 days after admission. AIS patients were divided into two groups according to their modified Rankin Scale (mRS) at 3 months after discharge: the low-mRS (mRS < 2) group included 48 patients and the high-mRS (mRS ≥ 2) group included 26 patients. The differences in %OxHSA and CRTAC1 between the two groups on days 0, 1, and 7 were evaluated.Results: The mean %OxHSA values of the high-mRS group on days 0, 1, and 7 were significantly higher than those of the low-mRS group (p < 0.05). The CRTAC1 levels continuously increased from day 0 to day 7, and those of the high-mRS group were significantly higher than those of the low-mRS group on day 7 (p < 0.05).Conclusions: These results suggest that higher %OxHSA and CRTAC1 are associated with poor outcomes in AIS patients. An index that combines %OxHSA and CRTAC1 can accurately predict the outcomes of AIS patients.